Analyzing education based on metaverse technology - Mustafa, Bahaa (Technium Social Sciences Journal, 2022)
The Metaverse is a post-reality universe, a perpetual multi-user environment that combines physical reality and digital virtuality. It is based on the convergence of technologies that enable multisensory interactions with virtual environments, digital objects, and people, such as virtual reality (VR) and augmented reality (AR). As a result, Metaverse is a web of social, networked immersive environments on persistent multi-user platforms. It allows for real-time, embodied user communication and dynamic interactions with digital artifacts. Its first incarnation was a web of virtual worlds between which avatars could teleport. The modern Metaverse includes social, immersive VR platforms that are compatible with massive multiplayer online video games, open game worlds, and AR collaborative spaces. The aim of the research is to thoroughly examine the perceptions and educational requirements of Metaverse-based education and to investigate its educational applicability. Using a mixed research method, the study investigated instructors' and students' perceptions of the use of the Metaverse in education, as well as the support system for classes that use the Metaverse. And determining the implications for action. plans and directions for its application in education.